ANALISIS KINERJA KEUANGAN DAN PEMBANGUNAN DAERAH TERHADAP PERTUMBUHAN EKONOMI DI GERBANGKERTASUSILA - Wahyu Himatul Aliya; Aris Soelistyo (Program Studi Ekonomi Pembangunan, 2020)
This study aims to determine how the effect of the Locally Generated Revenue (PAD), balance fund, government capital expenditure, Human Development Index (HDI), and labor force total (AK) on economic growth. This study used secondary data from 2008 until 2017. Analysis techniques is quantitative, which use Panel Regression Method. Analysis results show that the estimation model analysis selected is Fixed Effect (FE). The results show that the PAD variable has a significant positive effect on economic growth. The others variable while balance funds, government capital expenditure, AK and HDI has a negative significant effects on economic growth in Gerbangkertasusila.